Peran Pengawas Pembina dalam Meningkatkan Mutu Pengelolaan Pembelajaran di TK Gugus 5 Bunga Krisan - Zefanya Octoberi; Nita Yuliana; Jane Ibrani Rumbekwan; Yoan Colina (Indo Publishing, 2026)
This study aims to analyze the role of supervisory officers in improving the quality of learning and institutional management at TK Gugus 5 Bunga Krisan. Theoretically, supervisory officers function as academic and managerial supervisors who are responsible for guidance, mentoring, evaluation, and the development of teachers’ and principals’ competencies. This research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings revealed that supervisory activities began with the preparation of systematic work programs and plans, including structured schedules for coaching and classroom supervision. In practice, the supervisor implemented coaching approaches adapted to the characteristics of each school and principal, making the guidance process more flexible and contextual. The discussion results indicated that the coaching activities increased teachers’ motivation to develop more varied and child-centered learning strategies and learning processes. In addition, the supervisor also acted as a mentor, facilitator, and motivator in assisting schools to adapt to policy changes and demands for educational quality improvement. Therefore, the role of the supervisory officer contributes to the sustainable improvement of learning quality and institutional management in early childhood education institutions.